Теория:

Так как  \(1\) дм= \(10\) см,  \(1\) см =\(10\) мм, то верно равенство: 
\(1\) дм = \(10\) см = \(100\) мм
Аналогично, из того, что \(1\) м= \(10\) дм,  \(1\) дм = \(10\) см следует равенство:
\(1\) м = \(10\) дм = \(100\) см
Приведём несколько примеров.
 
Пример:
1) \(6\) дм = \(600\) мм так как \(1\) дм = \(100\) мм

 
2) \(310\) см = \(31\) дм так как  \(100\) см = \(10\) дм

 
3) \(32\) см = \(320\) мм  так как  \(10\) см= \(100\) мм

 
4) \(2\) м \(54\) см = \(254\) см  так как \(1\) м = \(100\) см

 
5) \(7\) м \(8\) см = \(7\)\(08\) см  так как  \(1\) м = \(100\) см

 
6) \(5\) м \(4\) дм = \(540\) см  так как  \(1\) м = \(100\) см, \(1\) дм = \(10\) см